Medication management review in Australia : an overview of the development, implementation and evaluation - Bell, J. Simon (Dosis : farmaseuttinen aikakauskirja, 2007)
Tiivistelmä.
Keywords: lääkehoito; arviointi; laatu; vaikutukset; medicinering; utvärdering; kvalitet; effekter; Australia; Australien